2020
DOI: 10.3399/bjgpopen20x101015
|View full text |Cite
|
Sign up to set email alerts
|

Change in the use of diagnostic tests in the management of lower respiratory tract infections: a register-based study in primary care

Abstract: Background: Differentiating between pneumonia and acute bronchitis is often difficult in primary care. There is no consensus regarding clinical decision rules for pneumonia, and guidelines differ between countries. Use of diagnostic tests and change of management over time is not known.Aim: To calculate the proportion of diagnostic tests in the management of lower respiratory tract infections (LRTIs) in a low antibiotic prescribing country, and to evaluate if the use and prescription pattern has changed over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…However, not only Danish GPs seem to use the CRP test frequently. A Swedish study has also found an increased use of CRP testing for patients with symptoms of an acute LRTI from 55% in 2006 to 62% in 2014 [21].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…However, not only Danish GPs seem to use the CRP test frequently. A Swedish study has also found an increased use of CRP testing for patients with symptoms of an acute LRTI from 55% in 2006 to 62% in 2014 [21].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This may explain why it was used more often for patients with longer symptom duration. The proportion of CXRs was high in the control group as compared to a recent Swedish register-based study where CXR was shown to be used in 12% of patients with pneumonia in primary care [28].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 53%
“…It was quite surprising that the use of CXR differed so much (5% vs. 88%). The low use of CXR in primary care contrasts with previous studies indicating a usage of 12–22% in cases of suspected pneumonia; however, the methodologies and study populations differ [ 19 , 20 ]. The finding suggests that emergency care routinely uses CXR when pneumonia is suspected.…”
Section: Discussionmentioning
confidence: 65%